Expression of cyclooxygenase-1 (COX-1) in labial salivary glands of Sjögren's syndrome - Tominaga, M (Blackwell Science Inc, 2000)
COX plays an important role in inflammatory diseases such as rheumatoid arthritis. To determine the role of COX in Sjögren's syndrome (SS), we examined COX expression in the salivary glands of SS patients. We examined 15 patients with SS and two normal subjects. Labial salivary gland tissue samples were analysed immunohistochemically using anti-COX-1 and COX-2 antibodies. All biopsy samples from 15 patients with SS were stained for COX-1. In contrast, COX-1 immunostaining was not detected in normal salivary gland tissues. Co-expression of COX-1 and CD68 was confirmed by mirror section technique and double antibody immunostaining. This finding indicated that COX-1-expressing cells in SS salivary glands were infiltrating macrophages. In contrast to COX-1 staining, only a little COX-2 immunostaining was observed in salivary gland tissues from SS patients. These data suggest that COX-1 expression on infiltrating macrophages may contribute to the inflammatory process of salivary glands in SS.